Outcomes-Based Education in Indonesian Higher Education: Empowering Students' Learning Competencies - Asbari, Masduki; Nurhayati, Wakhida (International Journal of Social and Management Studies, 2024)
Outcomes-Based Education (OBE) has been increasingly adopted in Indonesian higher education institutions, reflecting a global trend toward competency-based learning approaches. This article explores the implementation of OBE in Indonesian universities, focusing on how it empowers students to develop essential competencies such as critical thinking, problem-solving, communication, and collaboration. Using a qualitative descriptive method, the study combines literature review, observations, and interviews with key stakeholders, including educators, administrators, and curriculum developers. The findings suggest that OBE enhances student learning outcomes, but challenges such as limited faculty training, inadequate infrastructure, and institutional resistance persist. The research highlights the need for targeted professional development for educators, greater institutional commitment, and alignment of curricula with OBE principles to fully realize the potential of this approach. This study provides practical recommendations for policymakers, administrators, and educators to strengthen the adoption and effectiveness of OBE in Indonesia. The insights gained from this research contribute to ongoing discussions about improving the quality of education in Indonesia through student-centered pedagogies.